Correlation of maternal hemoglobin with outcome of neonatal gestational age and birth weight - Ramya, H. S.; T. C., Rajendra Prasad; A. R., Nisar Ahamed; Awati, Muragesh (International Journal of Contemporary Pediatrics, 2019)
Background: Anemia is the most common nutritional deficiency disorder in the world. Maternal anemia has become one of the major health concerns worldwide. It is associated with adverse maternal and fetal outcomes such as increased rates of maternal and perinatal mortality, premature delivery, low birth weight and certain anomalies. This study was done to find out the correlation between maternal hemoglobin and birth weight and gestational age of newborn at birth. Methods: This is an observational clinical study, which included 1501 pregnant mother and their newborn babies. All singleton live born babies born were examined. The pregnant women’s lowest recorded hemoglobin measurement during pregnancy is correlated with outcomes of neonatal gestational age and birth weight. Results: Majority of the mothers belonged to lower middle class. 59.4% of the mothers were anemic. 21% of the babies born were preterm and 30% of the babies born were low birth weight. Conclusions: In India, according to WHO 2018 data, anemia in pregnancy is 65-75%. Present study outcome shows, preterm deliveries is 12.1% and low birth weight is 17.8% born to anaemic mothers who were 59.4%. The reduction in percentage of anaemic mothers in current study is due to National health programmes. In future, these programs will help to reduce the incidence of anaemia in pregnancy, which in turn will reduce low birth weight and preterm deliveries.